The Effectiveness of a Training Program in Developing Cognitive Competencies of Media Professionals about Autistic Children using a Jordanian Sample - Khalil Al-Zyoud (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The purpose of this study is to investigate the effectiveness of a training program in developing cognitive competencies among media professionals toward children with autism spectrum disorder (ASD) in a Jordanian sample. Additionally, the study explored if there were significant differences due to visual, audio, and read media. This study utilized the quasi-experimental approach to assess the effectiveness of the training program in developing cognitive competencies of media professionals. The sample of the study consisted of (60) media professionals selected randomly from the employees of many media organizations divided into reading, audio, and video professionals (10 each). A scale with high reliability and validity scores was developed by the researcher to measure cognitive competencies. The scale consisted of 63 items across six domains: definition of ASD, general concepts about ASD, theories explaining ASD, characteristics of ASD, early screening and diagnosis of ASD, and differential diagnosis of ASD. The training program was implemented through 10 training sessions, for 60 minutes for each session, over a period of 15 training days. The findings of the study showed that there are significant statistical differences between the pre and post-measures in all domains of the scale attributed to the training program. There were no significant statistical differences in the post-measure of cognitive competencies according to the type of media in all sub-domains of the cognitive competencies scale. The study emphasizes the need for conducting more studies on larger samples covering all areas in Jordan, representing more disability categories.